Technology evaluations are associated with psychological need satisfaction across different spheres of experience: an application of the METUX scales - Burnell, Ryan; Peters, Dorian; Ryan, Richard M.; Calvo, Rafael A. (Frontiers in Psychology, 2023)
Digital technologies have the capacity to impact psychological wellbeing in both positive and negative ways. Improving technologies with respect to wellbeing requires nuanced understanding of this impact and reliable ways to measure it. Across two experiments with 1,521 participants, we investigated the relations between psychological needs and people’s evaluations of technologies (with respect to satisfaction, usability, and measures of value). To do so, we improved and validated four scales, first put forward as part of the METUX model of technology interaction, that measure psychological needs at the life, behavior, task, and interface levels. Each of these scales had good psychometric properties when applied to four separate technologies (Facebook, TikTok, Blackboard, and Moodle). At each of the four levels, psychological need satisfaction and frustration were associated with standard measures of usability and user satisfaction, and correlation patterns supported the METUX model and its approach to differentiating spheres of technology experience.